Deteksi Penyakit Pada Daun Cabai Menggunakan Metode Convolutional Neural Network - Firdaus, Usamah Putra; Litanianda, Yovi (Universitas Multi Data Palembang, 2024)
Chili peppers are one of the most popular vegetable crops among the Indonesian population. According to BPS data, both the consumption and production levels of large chili peppers and bird's eye chili peppers in 2022 exceeded those of previous years. Despite the high production levels, cultivating chili peppers is very risky due to frequent attacks by diseases and pests. Therefore, a system that can identify diseases or pests in chili pepper plants is needed. In this study, classification is divided into four categories: Healthy, Whitefly, Yellowish, and Leaf Spot. The method used is Convolutional Neural Network (CNN). The accuracy achieved from the training data is 88%, while the validation data accuracy is 82%. After conducting ten trials for each category, good accuracy was obtained. The Healthy category achieved 100% accuracy, Whitefly 70%, Yellowish 80%, and Leaf Spot 90%